Estimation of Aerodynamic Characteristics of a Light Aircraft - Ishak, Iskandar Shah; Mat, Shabudin; Mat Lazim, Tholudin; Muhammad, Mohd. Khir; Mansor, Shuhaimi; Awang, Mohd Zailani (Faculty of Mechanical Engineering, 2006)
This paper presents the aerodynamic estimation carried out on a three-dimensional aircraft model by conducting wind tunnel tests and Computational Fluid Dynamics (CFD) simulation. The test model is a 15% scaled down from a two-seater light aircraft that is closed to the Malaysian made SME MD3-160 aircraft. This aircraft model has been tested at two different low speed tunnels, namely at Universiti Teknologi Malaysia’s tunnel (UTM-LST) test section sized of 2.0 x 1.5 m2, and at Institute Aerodynamic Research, National Research Council of Canada (IAR-NRC) sized 3.0 x 2.0 m2 tunnel. The speed during testing at UTM-LST and IAR-NRC tunnels was up to 70 m/s, which corresponds to Reynolds Number of 1.3 x 106. The longitudinal and lateral directional aerodynamic characteristics of the aircraft such as coefficients of pressure, forces (lift, drag and side force) and moments (roll, pitch and yaw moment) had been experimentally measured either using direct force measurement or pressure measurement method. The data reduction methods included the strut support interference factor using dummy image and the blockage correction had been applied in this wind tunnel tests. On top of the experimental study, simulation was also performed using a commercial CFD code, FLUENT. Experimental works at UTM-LST and IAR–NRC tunnel showed that the aerodynamic characteristics of this light aircraft were in good agreement with each other. Simultaneously, the aerodynamic forces obtained from the experimental works and CFD simulations had been compared. The results proved that they were agreeable especially at a low angle of attack.